Perseteruan Memori Kolektif: Kontestasi Islam dan Politik di Tasikmalaya Pasca-Orde Baru - Mudzakkir, Amin (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This paper aims to understand the post-New Order political Islam, by taking the case in Tasikmalaya from its historical and reactualization perspective. Maurice Halbwachs and Pierre Nora called the last thing as a memory, which is considered the antithesis of history. In practice, the boundary between history and memory is indeed blurred or obscured. For the analysis in this paper, these two things are positioned differently. The focus of the article is to understand the extent to which democracy works in local cultural values which may conflict with the views of liberal human rights. The case of Tasikmalaya is interesting to put in the context of “democratic communitarianism” and more broadly can be used to see tolerance in Indonesia through the lens of cooperation between universal human rights principles and religious interpretations that are grounded in communal experience.